Projected losses of ecosystem services in the US disproportionately affect non-white and lower-income populations - Jesse D. Gourevitch (Nature Portfolio, 2021)
Social inequalities may be reflected in how ecosystem services are distributed among groups of people. Here the authors estimate the distribution of three ecosystem services across demographic and socioeconomic groups in the US between 2020 and 2100, finding that non-white and lower-income groups disproportionately bear the loss of ecosystem service benefits.